A Critique on the Book Microeconomics Analysis - Hassan Heydari; Hassan Mirzaei (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Translation is one of the most important tools for knowledge transfer, especially for the academic community, so translation of a book like its original version has a special value and importance. One of the most valuable and academic books is "Microeconomic Analysis" which is written by Hal.R Varian which is one of the top scientific sources of microeconomics. Ney Publishing has published this book which is translated by Mr. Reza Hosseini and now it is one of the educational resources of microeconomics in postgraduate studies in Iranian universities. Given the valuable position of this book, its translation requires a critical review and this article has tried to evaluate the weaknesses and strengths of this book according to the analytical-descriptive method by quantitative and qualitative analysis. It means discussing the appearance features, writing, edition, idiomatic translations, and text translation. It has been concluded that the translation of this book is quantitatively acceptable, but it has qualitative disadvantages that are not sufficient for the translation of an academic scientific book. It is suggested that due to the numerous editions of the book's translation and its importance, the next editions of this translation should be reviewed and the proposed corrections can be considered.